2012
DOI: 10.1128/mcb.00010-12
|View full text |Cite
|
Sign up to set email alerts
|

Protein Landscape atDrosophila melanogasterTelomere-Associated Sequence Repeats

Abstract: eThe specific set of proteins bound at each genomic locus contributes decisively to regulatory processes and to the identity of a cell. Understanding of the function of a particular locus requires the knowledge of what factors interact with that locus and how the protein composition changes in different cell types or during the response to internal and external signals. Proteomic analysis of isolated chromatin segments (PICh) was developed as a tool to target, purify, and identify proteins associated with a de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…Interestingly, some classical heterochromatic marks are also present: H3K9me3 and HP1a are enriched at the TAS in third instar larvae. These findings are supported by a recent proteomic analysis of isolated chromatin segments, which found SU(VAR)3-9 (one of the three H3K9 methyltransferases) along with TRL and PC (Polycomb system components) associated with the TAS sequences (Antao et al 2012). As noted above, PEV studies have found that inserts into the TAS are generally unaffected by mutations in HP1a [i.e.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, some classical heterochromatic marks are also present: H3K9me3 and HP1a are enriched at the TAS in third instar larvae. These findings are supported by a recent proteomic analysis of isolated chromatin segments, which found SU(VAR)3-9 (one of the three H3K9 methyltransferases) along with TRL and PC (Polycomb system components) associated with the TAS sequences (Antao et al 2012). As noted above, PEV studies have found that inserts into the TAS are generally unaffected by mutations in HP1a [i.e.…”
Section: Discussionsupporting
confidence: 61%
“…150,151 Interestingly, in a recent screen Drosophila Dek was identified as a novel factor that could bind to telomere-associated sequence (TAS) repeats. 152 Although definitive studies have not been performed to elucidate the molecular functions of DEK specifically in stem and progenitor cells, growing evidence that changes in DEK expression impact several crucial pathways is suggestive that DEK, too, may be fundamentally important for the viability and function of the stem and/or progenitor cell populations. Combined, DEK either regulates or is regulated by several signaling pathways and transcription factors implicated in stem cell proliferation, differentiation and self-renewal, potentially through its roles in regulating chromatin topology (Fig.…”
Section: Dek Regulates Chromatin Structure and Function In Normal Andmentioning
confidence: 99%
“…Association of DEK with telomeres has been reported in Drosophila (Antao et al 2012). However, it is important to note that not all telomeres contain DEK in mouse ESCs.…”
Section: Dek Is Important To Preserve Telomeric Chromatin Integritymentioning
confidence: 96%